Pengembangan Komposit Bermatrik Ebonit Dengan Kandungan Sulfur 30 Phr Yang Diperkuat Serat Kelapa Untuk Komponen Otomotif - Anggi Prasetyo, Dika; , Joko Sedyono, ST, M.Eng, Ph.D; , Ir. Agus Hariyanto, MT (2016)
This study was aimed to determine the strength of the composite using a variation of fiber weight 0 phr, 30 phr and 50 phr by conducting a tensile test to ASTM D638, Izod test impact with ASTM D256, hardness test with the standard ISO 0778: 2009 and SEM photo by using JEOL JSM-6510LA tool. Composite materials used were ebonite as a matrix with coconut fiber reinforcement. The first process performed was the selection of coconut fibers which then cut as length as 20 mm and then fibers were soaked with NaOH 5% per 1 liter of distilled water with immersion time for 2 hours, after soaking finished coconut fibers were dried until the moisture content comes to 8%, then the process of compound production was ended by mixing natural rubber of chemicals materials and fibers using a two-roll mill, and then the vulcanizing was processed by using the hot press print method (hot press mold}. The results of the study showed that by the maximum tensile strength fiber composite with a weight of 30 phr with a voltage of 6.20 N / mm2, the maximum strain on the composite with 30 phr fiber weight by 84%. Average Izod impact testing ensued the highest average fiber weight 30 phr of 29.57 J / mm2, for the average hardness test results obtained the highest average fiber weight of 73.100 scale of 0 phr shore A and the SEM images obtained from composites with fraction of fiber weight 0 phr had the best structure. Keywords: composite, ebonite, coconut fiber, two roll mill, vulcanization